Preparation of Flame-Retardant Membrane Materials by In-Situ Loading of Mg(OH)₂ on Cellulose Hydrogel from Low-Concentration MgCl₂ Solution - Rokhati, Ahmad; Kemefa, Peter; Arantes, Luidy (Journal of Green Energy and Environmental Engineering, 2025)
This paper selects absorbent cotton as the cellulose raw material, uses a low-temperature alkaline urea solution as the dissolution system to dissolve the absorbent cotton and then regenerates it to obtain regenerated cellulose hydrogel. Lower concentration magnesium chloride solutions (0.01 mol·L⁻¹, 0.05 mol·L⁻¹, 0.10 mol·L⁻¹, 0.15 mol·L⁻¹, 0.20 mol·L⁻¹) and sodium hydroxide solution are selected to in-situ load magnesium hydroxide onto the regenerated cellulose hydrogel through the precipitation reaction of magnesium ions and hydroxide ions. After drying, magnesium hydroxide/regenerated cellulose composite membrane materials are finally prepared. The experimental results are characterized using optical microscopy, scanning electron microscopy, and combustion performance tests. The study finds that when the absorbent cotton content is 3 wt.%, the cellulose solution concentration is moderate, facilitating uniform coating and film formation. Lower concentration in-situ loaded magnesium hydroxide has a good effect on the flame retardancy of regenerated cellulose. The reaction solution concentration significantly affects the microscopic morphology of magnesium hydroxide precipitation. When the magnesium chloride concentration is 0.05 mol·L⁻¹, the precipitation loading is uniform and has nano-scale micro-protrusion structures; at concentrations of 0.10 mol·L⁻¹ and 0.15 mol·L⁻¹, micro-prismatic flaky structures can be observed. Moreover, when the magnesium chloride reaction solution concentration is 0.15 mol·L⁻¹, the theoretical loading mass fraction of magnesium hydroxide is 19.68%, the sample's average flaming time is 0 s, average glowing time is 3.83 s, and average char length is 3.83 mm, demonstrating the best flame retardant effect.